Perancangan dan Pembuatan Aplikasi Sistem Kearsipan Elektronik Berbasis Microsoft Access pada Unit Simpan Pinjam Koperasi Warga Polban (KWP) : Pengabdian - Tresna Karomatan; Marwansyah, Marwansyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aimed to develop an electronic archiving system application based on Microsoft Access for the Savings and Loan Unit of Koperasi Warga Polban (KWP), which had previously encountered various challenges in managing manual archives, such as limited storage space, search times reaching 10–15 minutes per document, and risks of document loss or damage. The system was designed using the waterfall method through several stages, starting from needs analysis, system design—covering the creation of use case diagrams to map user interactions, flowcharts to visualize workflows, and entity relationship diagrams (ERD) for database structure. At the implementation stage, key features were developed, including input forms for incoming and outgoing mail, document management for savings and loans, archiving of internal and legal documents, and a search feature that enabled document retrieval in under one minute. The system testing results showed an improvement in work efficiency with a reduction in search time by up to 93%, increased data accuracy through automated validation, and enhanced data security with authentication systems and routine backup mechanisms. Evaluation through comparative tests and interviews with administrative staff regarding high user satisfaction with the ease of the interface, completeness of features, and stability of the system.